Phenol Biosensor Based on Glassy Carbon Electrode Directly Absorbed Escherichia coli Cells with Surface-displayed Bacterial Laccase. (2017) - Zhang, Zhen; Zhang, Zhongming; Hu, Yonggang; Liu, Jin; Ni, Hong; Li, Lin
Abstract: In this study, a new biosensor was developed based on a bacterial laccase immobilizing on Escherichia coli surface and direct glassy-carbon electrode adsorption of live cells. Expression and surface localization of laccases in target cells were confirmed by assays of Western blot, immunofluorescence microscopy and flow cytometry. The engineered cells served as a highly active whole cell laccase-catalytic system with an enzyme activity of 32.7 U/mL cells. Under optimized pH condition, electrochemical response of the biosensor was linear within concentration ranges of 5.0 μM to 500.0 μM for several phenolics (catechol, caffeic acid, dopamine, gallic acid, and 2-amino phenol) with a detection limit of 1.0 μM to 5.0 μM, which was comparable to those based on chemically-modified purified laccases. The system exhibited good stability and reproducibility. It also offered considerable level of accuracy for determination of the phenolic compound contents of wed wine, pharmaceutical and wastewater samples.